1998
DOI: 10.1046/j.1365-2605.1998.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Lectin histochemistry of the human testis

Abstract: The oligosaccharide sequences of glycoconjugates and the nature of the saccharide linkage were investigated in normal human testes by means of lectin histochemistry studies, at light and electron microscopy levels. Reaction to WGA was intense in the seminiferous epithelium and interstitium. MAA showed light reactivity in all cell types of the human seminiferous epithelium, the lamina propria and Leydig cells. UEA-I lectin labelled the lamina propria intensely and the seminiferous epithelium and Leydig cells sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
3
45

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(89 citation statements)
references
References 31 publications
6
35
3
45
Order By: Relevance
“…Therefore, such differences in lectin bindings in the acrosomal region may reflect different acrosomal components of sugar residues in each mammalian species. In contrast to the variation in lectin bindings in acrosome, PNA had a conserved binding pattern in the acrosomal region of all mammalian species examined so far [1][2][3][4][5][6][7][8][9][10][11][12][13]. In concurrence, the present study also showed an intense reaction in the acrosomal region of bats.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Therefore, such differences in lectin bindings in the acrosomal region may reflect different acrosomal components of sugar residues in each mammalian species. In contrast to the variation in lectin bindings in acrosome, PNA had a conserved binding pattern in the acrosomal region of all mammalian species examined so far [1][2][3][4][5][6][7][8][9][10][11][12][13]. In concurrence, the present study also showed an intense reaction in the acrosomal region of bats.…”
Section: Discussionsupporting
confidence: 76%
“…The UEA-I reaction, representing the appearance of α-Fucose residues, have been reportedly detected in the acrosomal region of the rat [5,6], mouse [7,8], nutria [8] and bull [12], but no reaction was or has previously been observed in the testes of the Java fruit bat, the Japanese lesser horseshoe bat, the guinea pig [9] or the musk shrew [10]. It has been demonstrated that SBA reacts strongly in the acrosomal region of many mammalian species, such as man [1][2][3][4], rat [5,6], mouse [7,8], nutria [8], guinea pig [9], common tree shrew [11], bull [12] and shiba goat [13], but this reaction could not be detected in either the Java fruit bat or the Japanese lesser horseshoe bat. The DBA binding pattern has varied among the various species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aplikasi yang sama juga dilakukan pada rodensia laboratorium (Söderström et al, 1987), testis manusia (Arenas et al, 1998), babi (Calvo et al, 2000), dan babi rusa (Agungpriyono et al, 2007). Dari data yang diperoleh pada penelitian terdahulu, ditemukan adanya modifikasi yang luas pada saat pembentukan spermatozoa yang diekspresikan oleh perbedaan pola ikatan antara glikokonjugat dan lektin.…”
Section: Pendahuluanunclassified
“…Plant lectins, which are most easily characterized by their affinities for specific, terminal glycosidic residues associated with glycolipids and glycoproteins, and c-kit, a known marker for mammalian spermatogonia, were evaluated for their possible use as markers for specific cell-types in the SE of the turkey. Lectins have been used to describe glycoprotein components of germ and somatic cells in the mammalian SE and to elucidate patterns of glycoprotein synthesis, secretion, and absorption in the cells of the mammalian SE and epididymis Vanha-Perttula, 1984, 1986a,b;Arenas et al, 1998;Pastor et al, 2003).…”
Section: Introductionmentioning
confidence: 99%